Comprehensive review on the composition, influence, and inhibition of asphalt fumes - Ke Shi; Feng Ma; Augusto Cannone Falchetto; Zhen Fu; Dongdong Yuan; Ruimeng Song; Jiasheng Dai; Haopeng Wang (Journal of Traffic and Transportation Engineering (English ed. Online))
Asphalt mixtures generate substantial amounts of harmful fumes and particulate matter (PM) during various construction processes, including factory mixing, vehicle transportation, and field paving. Road workers exposed to asphalt fumes face potential health hazards, while the emissions also adversely affect the atmospheric environment. Investigation into the determination of asphalt fume components, the impact of exposure, and inhibition strategies have gained significant attention. This paper conducted an analysis based on the publications from 1998 to 2024 on asphalt fumes, elucidating the knowledge landscape of asphalt fume research. The cooperative features, literature classification, and journal sources in the field are systematically examined. Current research focuses on topics such as composition and emission characterization of asphalt fumes, collection and detection of asphalt fumes, exposure to asphalt fumes and their health effects, and sustainable asphalt technologies and emissions control. Additionally, this paper proposes trends in the asphalt fume research field; it outlines future research directions, offering theoretical guidance for studying the impact and inhibition of asphalt fumes.